Diálogos e práxis de um literato: uma interpretação do pensamento político-social de José de Alencar - Simões, David Soares (2012)
This research intends to analyze the political writings of Jose de Alencar (1829-1877) with the objective of mapping his forms of thought and his political practice. The first analytical effort focuses on the ideas of the novelist, outlining possible dialogs between Alencar and some thinkers of the political theory (Benjamin Constant, Stuart Mill, Alexis de Tocqueville and John Locke) and verifying to what extent his ideas would find one application limit in the context of the nineteenth-century Brazil. Then it tries to evaluate the praxis of the literate from the Cartas de Erasmo (Letters of Erasmus), considering them as a strategy of political action in the 1860s. It is argued that the political ideas printed on the letters would express a broader set of positions assumed by him along his political career, which would reveal his choice for and his affiliation to the more orthodox conservative political side that of the Saquaremas. Finally, in a confluence between theory and practice, will be highlighted the place of the ideas of José de Alencar. Counterpointing the interpretation according to which the novelist‟s ideas would be out of place, it is argued that they would conform to a specific context of elaboration and would express themselves in a conservative discourse tributary of the Saquaremas‟ model of political direction.